A redução de danos na problemática do álcool, crack e outras drogas sob a ótica dos profissionais do núcleo de apoio à saúde da família no município de Fortaleza - Rodrigues, Cristiane Nascimento de Aguiar (2016)
The abusive use of alcohol, crack and other drugs stands out in Brazilian society as a serious public health problem. In this sense, it is essential to understand how drugs are contextualized in the lives of individuals and to develop, in partnership with them, a more appropriate therapy. One of the possible strategies is Harm Reduction (DR) that defends the idea of ​​the person's participation and their autonomy in achieving better levels of health. In general, the health professionals of Primary Care confront themselves daily with the demands imposed by the use of psychoactive substances. In this context, the general objective is to analyze the knowledge and practices of Harm Reduction developed by professionals of the NASF in the Municipality of Fortaleza, Ceará, about the problem of the use of Alcohol, Crack and other drugs. This is an exploratory and descriptive research, with a quantitative approach, being part of the data collection of the umbrella project "Conceptions and actions of professionals of the Family Health Support Nuclei - NASF on Mental Health, Drugs ( Crack, alcohol and other drugs) and Reducing Harm in Primary Care. " The research was carried out with 19 NASF professionals working in the city of Fortaleza-CE, in the period of Jul / Dec / 2015. A semi-structured interview script was used to obtain the data that were statistically treated using the Statistical Package for Social Sciences (SPSS), distributed in tables with univariate and bivariate analysis. The results showed that although NASF professionals report performing Mental Health actions and RD practices, knowledge about this strategy presents weaknesses and restricted academic backgrounds. Most of them have stigmatizing and ambivalent positions disarticulated from the RD proposal, with significant influence of the traditional prohibitionist model, under the logic of abstinence. It is concluded that there are limitations in the actions of these professionals regarding the possibilities of adopting the Proposal, being able to restrict more comprehensive initiatives about the care to the users. Therefore, the importance of more drug studies focused on the Harm Reduction Strategy with the professionals that compose the Primary Care network is verified.